Pressões e volumes pulmonares em idosos institucionalizados - Borges, Juliana Bassalobre Carvalho [UNESP]; Dos Santos, Danilo Fernando; Munhoz, Flávia; De Carvalho, Sebastião Marcos Ribeiro [UNESP] (My University, 2015)
In the aging process there are system alterations, in the respiratory system this determines a pulmonary function decrease. The study aimed at investigating the pulmonary volumes and pressures of elderly people institutionalized in Tupã, and at evaluating its relation with: gender, age, smoking and physiotherapy. Thirty elderly people, both sexes, were studied; average age: 73.6 ± 12.3 years. They were submitted to an evaluation including personal data and backgrounds; and to specific tests to evaluate maximum respiratory pressures (PImax and PEmax) by manuvacuometry and minute volume (Mv), current volume (CV) and vital capacity (VC) by ventilometry. The statistical analysis was performed by test t and by Pearson correlation; a 5% level was adopted. Values beneath the predicted ones were observed for PImax (43.6 ± 30.5 cmH2O) and PEmax (45.8 ± 23.6 cmH2O) variables. A statistically significant result (p < 0.05) in the relation of gender with PImax, PEmax, Mv and CV was observed; men obtained best results. In comparing physiotherapy and the pressure/volume variables, a significant result (p < 0.005) was observed for maximum respiratory pressures. Significant correlations were observed among the Mv, CV and VC variables. The results suggest that the people studied present respiratory muscular debility and that physiotherapy has a beneficial influence on the respiratory muscular force performance. This population did not reach the values predicted by the literature regarding the pulmonary pressures and volumes.
Pulmonary pressures and volumes in institutionalized elderly people